Stability analysis of points in geodetic monitoring networks using the MINQUE method and the weighted similarity transformation - Ortiz, Eulalio; Marcano, Adonis; Leal, Julio (Rev. Téc. Fac. Ing. Univ. Zulia)
In the analysis of geodetic networks used for monitoring deformations, there are two baste aspects to consider. One is the correct estimation of the weights of the observations, and the other is the correct Datum definition. Not considering these aspects generates biased displacements and consequently, the analysis for the interpretation of the object’s deformation will be significantly distorted. Based on the theory of optimization, the MINQUE method permits an optimum estimation of the variance and covariance error model components of the observations in a geodetic network.”¢Based on the theory of projection, the weighted similarity transformation is used to define the Datum of the monitoring network, identifying the points that remain stable between two periods of measurements. The joint application of these two methods permits an optimal estimation of point displacements in geodetic monitoring networks. Their application to a network installed in the Boconó fault in the Boconó District demonstrates the pertinence of their utilization.